Cadaveric study using radio-opaque contrast to determine arterial communication between the two bellies of gastrocnemius muscles - Pawan Agarwal; K. L. Gupta; P. Yadav; Dhananjaya Sharma (Indian Journal of Plastic Surgery)
Introduction: Gastrocnemius muscle is a workhorse flap to cover upper third tibial defects but has a limitation in covering middle one-third tibial defects. The inferiorly based hemi gastrocnemius muscle flap can be useful for reconstruction of the middle third of the leg. The arterial communication between the gastrocnemius muscle heads has been demonstrated, the consistent location, however, was not studied in large specimens. Materials and Methods: This study was conducted on sixty specimens of gastrocnemius muscles harvested from thirty fresh cadavers to determine arterial communication between two heads of gastrocnemius muscle using radio-opaque contrast with future application of taking one head of muscle distally based for coverage of middle third defect of tibia. A total of 60 specimens were obtained from thirty fresh cadavers. In thirty specimens, medial sural artery ligated and divided and 20 ml iohexol (350) given through popliteal artery. In remaining thirty specimens lateral sural artery ligated and divided and 20 ml iohexol (350) given through popliteal artery. Digital X-rays of gastrocnemius muscle specimens were taken, and collaterals between two bellies in lower half were noted and the distance of collaterals from the muscles top edge was also noted. Results: We found the communications between both bellies of the gastrocnemius muscle in all specimens in both legs. The mean distance of communications from the upper edge of the medial belly was 15.88 cm and from upper edge of the lateral belly was 14.72 cm in the right leg, respectively. The mean distance of communications from upper edge of the medial belly was 16.01 cm and from upper edge of the lateral belly was 13.78 cm in the left leg. The distal communications between gastrocnemius bellies were not constant in their location, but all the connections were present in distal 3.79 cm of raphe. Conclusion: This study supports the future application of inferior-based hemigastrocnemius muscles flap to cover defects of middle third leg. When distally based hemigastrocnemius flap is planned roughly 1/3rd of distal attachment or distal 3.79 cm of connection between raphe should be maintained to preserve the vascular communications between the two bellies.